Pengaruh Kualitas Produk, Harga, dan Promosi terhadap Keputusan Pembelian Produk Plastik pada Pelanggan PT X - Irnawati Simanjuntak; Indra Muis (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the effect of product quality, price, and promotion on the purchasing decisions of wholesale customers of CV Mitra Saputra, a plastic products distributor in Bekasi City. It was motivated by fluctuating sales amid intensifying competition among plastic distributors, and by inconsistent prior findings on how product quality, price perception, and promotion shape purchasing decisions. A quantitative survey design was used, with data collected via a Likert-scale questionnaire distributed to 110 wholesale and retail customers, determined using the Slovin formula from a population of 150 regular customers through purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS version 27, preceded by validity, reliability, and classical assumption tests. Results show that product quality (t = 4.564; sig. = 0.000), price (t = 2.840; sig. = 0.005), and promotion (t = 4.437; sig. = 0.000) each positively and significantly affect purchasing decisions, jointly explaining 41.2% of the variance (F = 24.763; sig. = 0.000), with product quality as the dominant predictor. Its novelty lies in examining B2B purchasing behavior in plastic packaging distribution, a context rarely studied compared to B2C research. CV Mitra Saputra should thus maintain product quality, competitive pricing, and strong promotion.